2008
DOI: 10.1577/t07-192.1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Effective Size in Populations of Hatchery‐Raised Red Drum Released for Stock Enhancement

Abstract: Genetic analysis of progeny from 13 spawning events occurring over a 2-week period in a Texas Parks and Wildlife Department (TPWD) hatchery for red drum Sciaenops ocellatus during the spring of 2002 and hatchery spawning and release records over the 2003 spawning season were used to estimate the average genetic effective size of an average spawn and an average hatchery-released population. The purpose of this study was to assess the potential for a Ryman-Laikre effect in the TPWD red drum stock enhancement pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 13 publications
1
47
0
Order By: Relevance
“…Estimated N e for local populations is roughly 10 2 -10 3 compared to a census size on the order of 10 6 adults [70][71][72]. Individual broodstock programs typically use 40-200 adults [71][72][73], but non-random contributions of different parents leads to relatively low hatchery N e [69,71,72].…”
Section: Box 4 Genetic Monitoring Of Commercial Releases: Red Drum Imentioning
confidence: 99%
See 1 more Smart Citation
“…Estimated N e for local populations is roughly 10 2 -10 3 compared to a census size on the order of 10 6 adults [70][71][72]. Individual broodstock programs typically use 40-200 adults [71][72][73], but non-random contributions of different parents leads to relatively low hatchery N e [69,71,72].…”
Section: Box 4 Genetic Monitoring Of Commercial Releases: Red Drum Imentioning
confidence: 99%
“…Individual broodstock programs typically use 40-200 adults [71][72][73], but non-random contributions of different parents leads to relatively low hatchery N e [69,71,72]. A detailed study of one Texas hatchery in one year estimated the hatchery N e to be 28-47 [71]. Hatchery fish had habitat usage similar to wild fish in Florida [74] but not in Texas [69].…”
Section: Box 4 Genetic Monitoring Of Commercial Releases: Red Drum Imentioning
confidence: 99%
“…The dissimilarity between decreases in N bc and N ec and corresponding reductions in genetic diversity metrics, when comparing this study to those based on semelparous species, is likely because red drum have about 35 year‐classes represented in the adult population, and so high proportions of stocked fish within a single year‐class typically have a small impact on the genetic diversity of the population. Similarly, Gold et al () also reported the potential of a Ryman–Laikre effect from stocking large numbers of red drum into a Texas estuary from small effective population sizes in the hatchery, but did not detect reductions in genetic diversity in the wild (Carson et al ). Ultimately, N bc and N ec are measures of the influences of stocking on the effective population size of individuals recruiting into the adult population.…”
Section: Resultsmentioning
confidence: 98%
“…No changes in genetic diversity of Pacific herring ( Clupea pallasii ) with spatiotemporal stable population structures were observed (Kitada et al., ; Kitada, Yoshikai, et al., ). The Texas red drum enhancement programme replaces ~25% of the broodfish with wild each year; nevertheless, the analysis suggested a potential R‐L effect (Gold, Ma, Saillant, Silva, & Vega, ; Karlsson, Saillant, Bumguardner, Vega, & Gold, ). In contrast, no effect on genetic diversity was reported in the stocked red drum population in the South Carolina (Katalinas, Brenkert, Darden, & Denson, ).…”
Section: Genetic Effects Of Hatchery Propagationmentioning
confidence: 99%